Innovative Value Chain: Solution to Enhance Company Performance During Covid-19 Pandemic MCO In Sabah - Sidah Idris; Nelson Lajuni; Al-Nasrie Weli; Siti Hajar Samsu; Charlie Albert Lasuin (Penerbit UMS, 2021)
When technology leaps forward, the internal “capability gap” between new technology requirements and what incumbent companies/industries can implement is often an issue. Misalignment between technology requirements and an organization’s ability to meet them can also exist outside a company’s boundaries. Digital adoption, especially among local companies are barely touching 20 per cent, and most manufacturing companies apply less than 50 per cent of automation. Malaysia has always scored among the highest in the region in terms of digital readiness, according to global surveys. Critical challenges include the lack of awareness, especially among local companies in terms of the impact of and benefits of keeping up with new technologies. It shows the level of technology usage is still very low within business operations especially in the supply chain that discourages the firm to digitalise their business. Thus, this study identified innovative value chain factors affecting company performance among local companies in Sabah particularly. This paper use Diffusion of Innovation (DoI) theory to introduce three variables that were proposed to help predict innovative value chain among local companies in Sabah namely: idea generation, idea conversion, and diffusion of innovation. This study employed a quantitative method approach by using a questionnaire as a tool to answer the study aims. Data was collected from local companies in Sabah regardless in manufacturing, services and agriculture industry was analysed using Structural Equation Modelling (SEM) via Partial Least Squares (PLS). The results and implications included in our study contribute to an expanded understanding of the innovation factors that influence company performance among local companies in Sabah.